Movimento de reordenamento das escolas rurais no município de Bela Vista de Goiás - Rocha, Carlos Antônio (2018)
This dissertation is the result of a research process and is linked to the State Educational, Policies and Institutions Research Line of the Pontíficia Universidade de Goiás, master's degree Program in Education, whose objective was to reconstruct the reordering movement of rural schools in Bela Vista de Goiás from the year 1980 to 2006, period in which the schools closed. The research problem can be delineated from the question: How was the rural school reorganization movement in Bela Vista de Goiás and what was the logic of the public policies of that time, highlighting the importance and the criteria of the creation of the Nucleus School Nicanor Gomes Pereira at Fazenda Matinha. This is a topic considered of extreme relevance in the research scenario in the area of Education, presenting itself as important to be debated and studied, considering the small number of studies carried out regarding it and the urgent need to think about and offer education of quality in the field for the rural population. The study had as its starting point historical dialectical materialism, as a conception of reality and world, assuring the principle that reality exists independent of the consciousness we have of it and that, therefore, the material conditions determine the consciousness with which we appropriate this reality. It is a qualitative research whose methodological procedures adopted were the bibliographical, documentary and empirical research. The study covers geographically the 10 microregions of the municipal. Through a semi-structured questionnaire, we obtained the perception of 44 subjects who participated in the process of which resulted in the rearrangement of rural schools. As a theoretical contribution, we used Arendt (2007, 2008), Arroyo, Caldart and Molina (2004, 2006, 2011), Bobbio (2000), Brzezinski and Santos (2015), Campos (2005), Chauí (2004), Enguita (1989), Freire (1987,1996), Gadotti (2008, 2011), Kuenzer (1990), Martins (2004), Marx and Engels (1991, 2007), Silva (2007), among others. We show that the implementation of a Field Education policy encompasses a complex process since the education offered to children, young people and adolescents residing in rural areas occurs mostly in urban schools that do not always articulate a curriculum with the reality of field. Few schools that still resist in rural areas do not offer an education in the field, but an education in the field. It became clear that education was "urbanized" in the countryside, but not with the same opportunities. The studies revealed that for most of the local community (parents and teachers), the process was authoritarian and did not consider the will of the majority, contradictorily, to what is understood as a democratic process. We find that there is legislation that guarantees the education of the countryside, with solid foundations, however, lacking public policies that concretise this right, which was denied throughout Brazilian history.